2011
DOI: 10.1007/s00213-011-2241-4
|View full text |Cite
|
Sign up to set email alerts
|

Rats preexposed to MDMA display attenuated responses to its aversive effects in the absence of persistent monoamine depletions

Abstract: Prior MDMA experience weakened the ability of MDMA to induce taste aversions. This attenuation of MDMA's aversive effects may occur with low doses that do not persistently alter monoamine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The precise mechanisms by which ethanol regulates MDMA‐induced behavioral changes are not yet clear. However, a large and growing body of evidence has demonstrated that activation of either D 1 ‐, D 2 ‐, or 5‐HT 2 ‐receptor contributes to the expression of behavioral changes, such as increases in locomotor activity, stereotyped behaviors, and reinforcing/rewarding and discriminative stimulus effects induced by psychostimulants including MDMA in animals 29–33 . Locomotor activity produced by psychostimulants could be suppressed by several compounds through non‐specific mechanisms, such as sedative effects.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms by which ethanol regulates MDMA‐induced behavioral changes are not yet clear. However, a large and growing body of evidence has demonstrated that activation of either D 1 ‐, D 2 ‐, or 5‐HT 2 ‐receptor contributes to the expression of behavioral changes, such as increases in locomotor activity, stereotyped behaviors, and reinforcing/rewarding and discriminative stimulus effects induced by psychostimulants including MDMA in animals 29–33 . Locomotor activity produced by psychostimulants could be suppressed by several compounds through non‐specific mechanisms, such as sedative effects.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MDMA induced dose-dependent taste aversions in both adolescent and adult animals (see also Albaugh et al, 2011; Lin et al, 1993; Lin et al, 1994), but aversions were significantly weaker in the adolescent subjects. Blunted taste aversions were evident in the doses at which the aversions were acquired, the rate at which the aversions were first evident and the degree of suppression (in both the one- and two-bottle assessments) displayed by the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, speculating that there might be differences in this aversive effect in various age groups must be made cautiously. This is especially the case for compounds such as MDMA for which the characterization of its ability to induce aversions is relatively limited (see Albaugh et al, 2011; Lin et al, 1993; Lin et al, 1994). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations